MODERN APPROACHES TO PREPARING FUTURE TEACHERS TO APPLY PEDAGOGICAL INNOVATIONS (Multidisciplinary Journal of Science and Technology, 2025)
The article examines modern approaches to preparing future teachers to apply pedagogical innovations in the educational process. The theoretical foundations are presented, and modern technologies and innovative strategies used in the system of professional training of teachers are analyzed. Special attention was paid to the digital educational environment, competency-based approach, individualization of learning, as well as foreign experience in teacher training